The Practice of Antibiotic Therapy of Severe Community-Acquired Pneumonia in Adults in Russian Multidisciplinary Hospitals - S. A. Rachina; I. A. Zakharenkov; N. N. Dekhnich; R. S. Kozlov; A. I. Sinopalnikov; M. V. Archipenko; S. A. Gordeeva; M. S. Lebedeva; U. S. Portnyagina; N. V. Dyatlov (Антибиотики и Химиотерапия, 2022)
Community-acquired pneumonia (CAP) is a common cause of hospitalization and mortality worldwide. A timely start and an adequate choice of the initial  antibiotic therapy (ABT) regimen are the key strategy  for optimizing the prognosis in severe  CAP.The aim was to study the practice of using systemic antimicrobial drugs (AMDs) in adults with severe CAP in multidisciplinary hospitals of the Russian Federation, as well as to assess compliance of initial  ABT with current  clinical guidelines.Methods. A prospective cohort study included adult patients with severe  CAP hospitalized in multidisciplinary hospitals in 6 Russian cities  during  the period  of 2014–2018. The adequacy criteria  of the initial  ABT for severe  CAP were: the prescription of combination ABT, the compliance of the selected initial ABT regimen with Russian clinical guidelines, and the intravenous route  of AMDs administration during  the initial  therapy. In addition, the frequency of using  switch  therapy and antimicrobial de-escalation was assessed.Results. A total of 109 patients (60.6% men; mean age 50.8±18.0 years) were included in the study. Hospital mortality was 22.9%. In all cases, AMDs were prescribed within  24 hours  after admission, antiviral drugs were used in 2.8% of patients. Levoﬂoxacin, ceftriaxone, azithromycin, amoxicillin/clavulanate were the most commonly used AMDs (prescribed in 14.4%, 12.5%, 11.9% and 10.7% of cases, respectively). Initial  combination ABT was prescribed in 50.5% of patients; in 80.2% of the cases, the medications were administered intravenously. The duration of treatment was 13.9±11.2 days. Initial ABT regimens complied with Russian Clinical  Guidelines in 37.6% of cases. Switch therapy and antimicrobial de-escalation was used in 11.9% and 3.6% of cases, respectively.Conclusion. Low adherence to Russian Clinical Recommendations regarding the regimens of initial ABT, as well as rare use of switch  therapy and antimicrobial de-escalation were revealed.